ANALISIS KEMAMPUAN PEMBUKTIAN MATEMATIS PADA MATAKULIAH TEORI BILANGAN - Nurrahmah, Arfatin; Karim, Abdul (JURNAL e-DuMath, 2018)
The number theory course focuses on the activities of reasoning, reviewing, analyzing, and proving, which is a high level of cognitive ability. Especially for of a lot of proof errors are done by students. The purpose of this research is to analyze the students of ability in the number theory course. The research method used is qualitative deductive research with research subjects amounted to 30 students semester three academic year 2017/2018. Data collection techniques use data triangulations. The results of mathematical proofing ability found that most of the students still have difficulty in solving the problem of proof. As many as 60% of the research sample has not understood how to solve the problem of proof. Based on these data, it can be concluded that the student has not be able to optimize all capabilities, especially the proof of mathematics in working on the number theory that tends to give up in working on problems when experiencing difficulties.